Do remittance flows promote financial inclusion? - Immaculate Machasio (Philipps-University Marburg, School of Business and Economics, 2018)
In this paper, we evaluate whether remittances promote financial inclusion in developing countries. We construct an index of financial inclusion and present single equation estimates of the effects of remittances on financial inclusion. The paper uses data on remittance flows to 61 developing countries from different regions around the world spanning from 1990-2014 to explore this nexus. The study uses fixed effects estimations as well as GMM IV estimation method of panel data econometric analysis. The regression results confirm the hypothesis that remittances have an impact on financial inclusion through their effect on financial sector development. This can be intuitively explained by the fact that sending and receiving remittances increase senders and recipients use of financial services. The study shows that indeed remittances increase financial inclusion by about 2.49%. Remittances can therefore be considered a catalyst of financial inclusion in development.
Keywords: C23; F34; H63; 330; Remittances; Financial inclusion; Instrumental variables